A medico-legal definition of femicide. (November 2022) - Cecchi, R.; Sassani, M.; Agugiaro, G.; Caroppo, E.; De Lellis, P.; Sannella, A.; Mazza, M.; Ikeda, T.; Kondo, T.; Masotti, V.
Highlights: Femicide deserves an unambiguous definition. Only a few countries have specific laws on femicide. International organizations stand against femicide. Femicide is the failure to recognize the victim's right to self-determination. There is a need for homogeneous methodology for the study of female homicides. Abstract: Femicide refers to the extreme form of violence against someone belonging to the female gender, i.e. the killing of a woman. Research shows that, to date, gender-based violence remains largely a hidden phenomenon with prevalence often being underestimated by official statistics and data missing in numerous countries. It can be argued that the under-reporting may be suggestive of a legislative gap that needs addressing. This work aims to reach a shared medico-legal definition of femicide stemming from a comprehensive review of the current legislation of countries around the world. In addition, it appraises forensic pathology studies focusing on the murder of women as well as the most relevant documents published by prominent international organizations fighting violence against women. Review of the literature shows a scarcity of national legislations concerning specifically femicide, despite the attention given to this phenomenon by international organizations fighting violence against women. Additionally, a non-homogeneous framing of the term femicide arises from the forensic pathology literature and national laws. Starting from one of the funding principle of medical ethics – autonomy – authors propose to define femicide as a murder perpetrated because of a failure to recognize the victim's right to self-determination. This definition would give the forensic pathologist a central role in identifying femicide cases among the murders of women. A shared forensic approach is needed, ideally employing standardized methodology to compare international data and to standardize scientific research in the field.